Managing novel therapies and concomitant medications in chronic lymphocytic leukemia: key challenges - Sofija Kozarac; Jelena Ivanovic; Marko Mitrovic; Kristina Tomic Vujovic; Isidora Arsenovic; Nada Suvajdzic-Vukovic; Nada Suvajdzic-Vukovic; Andrija Bogdanovic; Andrija Bogdanovic; Ana Vidovic; Ana Vidovic; Milena Todorovic-Balint; et al. (Frontiers in Pharmacology)
The treatment of chronic lymphocytic leukemia (CLL) consists of the continuous use of Bruton tyrosine kinase inhibitors (BTKis) such as ibrutinib, acalabrutinib, zanubrutinib and pirtobrutinib, or Bcl-2 inhibitors, such as venetoclax. Overall survival (OS) and progression-free survival (PFS) of CLL patients are significantly improved with the use of these therapies. Adverse effects (AEs) that can occur during treatment and the presence of pre-existing comorbidities in patients can influence subsequent treatment outcomes and, consequently, OS and PFS. Managing these AEs, including cardiologic toxicity and infections (including fungal infections), as well as treating cardiovascular and other comorbidities, can be challenging due to potential drug interactions with the medications used for the management of AEs and comorbidities. Therefore, this review examined the key challenges associated with the concomitant use of novel CLL therapies and medications for managing comorbidities and AEs. This review aims to enhance and facilitate the management of patients with CLL.